LA «GLOCALIZACIÓN» COMO RASGO DEFINITORIO DEL REMAKE TRANSCULTURAL EN TELEVISIÓN - Dra. Isadora GARCIA AVIS (Fonseca, Journal of Communication, 2023)
In the current «Golden Age» of television, transcultural remakes of scripted formats are becoming increasingly more prevalent on television screens all over the world. In spite of this, this phenomenon has yet to be examined from a theoretical perspective. Therefore, the aim of this study is to approach the notion of remake (and, more specifically,of transcultural remakes in television) from a conceptual standpoint. First of all, in order to explore the nature of remakes, it is deemed necessary to review existing bibliography in the field of cinematic remakes, where the term first appeared. With the goal of establishing a more comprehensive view of this concept, the theoretical findings are combined with interviews with television screenwriters, producers and executives, who provide a more practical point of view of the ways in which the term remake is used within the industry. Secondly, this article offers a review of different typologies and categorizations of remakes, highlighting the specificity of transcultural remakes in television. Lastly, this research manages to prove that the process of glocalization (that is, the dialogue between the global and local components of any given television format) emerges as a defining trait of this distinctive form of adaptation